ERADICATING THE BARRIERS TO INCLUSIVE HIGHER EDUCATION - E. E. Zorina (Obrazovanie i Nauka, 2018)
Introduction. Nowadays, people with disabilities (PWDs) and special educational needs must be empowered with high-quality university education for successful social integration in life. However, the current restricted access to inclusive higher education makes it hard to enhance their professional fulfillment and to find their role and place in the modern society.The aim of the research is the search for the answer how to eradicate barriers to inclusive higher education in the Russian universities.Methodology and research methods. The research is based on inclusive approach to education that enables to adapt the high school system of preparation for individual educational needs of students. The publications on the studied subject was analysed; the experience of the organization of inclusive education in foreign and Russian higher education institutions is studied and generalized.Results and scientific novelty. The attitudinal, physical, and academic barriers to inclusive higher education introduction and effective implementation in the Russian Federation are revealed and described in detail. The methodology of sustainable elimination of these barriers including preliminary evaluation, preparatory, final evaluation and activity stages is offered. The purposes of elimination of each of barriers are opened. Overcoming a physical barrier (by means of re-planning of buildings, re-equipment of classrooms and technical facilities) assumes creation of the inclusive infrastructural environment for the most comfortable training, communication and socialization of students with special educational needs. Full academic access to high-quality education means existence of the adapted educational programs, individual approach to training of PWDs, their psychological and pedagogical support from the faculty and other members of higher education institution. The attitudinal barrier involves socio-rehabilitational and correctional support as well as a complex of actions for socialization of students and development of their interpersonal communication. The question of attitudinal barrier is not appropriately covered by the Russian researchers. Therefore, the author emphasizes the need for overcoming the attitudinal barrier that is caused by the objectives of continuous self-improvement of students with special needs and development of their competitiveness. Furthermore, this barrier significantly influences physical and academic restrictions.Practical significance. The presented action framework for assistance of free access of people with disabilities to high-quality educational services will contribute to personal economic independence of this category of citizens, their successful socialization and professional fulfillment in the future. The research findings could be applied to any levels of professional training in various directions and specialties.